Climate change adaptation and mitigation strategies in Poland : a study of the forest carbon farms project’s (Leśne Gospodarstwa Węglowe) implications for biodiversity - Lozinski, Antoni (SLU/Southern Swedish Forest Research Centre, 2020)
Climate change is affecting forests in Europe. In response, Polish State Forests developed the Forest Carbon Farms project (FCF) which involves a range of climate change adaptation and mitigation strategies (CCAMS) for adoption. Those strategies are meant to change the current forest management in Poland. However, there is no research done on how these changes might affect key habitat determinants of biodiversity Polish forests. In this work I evaluate which of these strategies are likely to positively or negatively influence habitat availability in the current forest state. To do so I summarized the most important biodiversity goals for forests in Poland, which are mentioned in the legislation and sustainable forest management standard, in relation to the possible outcomes of each CCAMS for these goals, which I sourced from the recent scientific literature. My results showed that some of the CCAMS already adopted in FCF are not consistent with Poland’s biodiversity goals. Further use of strategies like Energy Wood Yards or fast-growing tree species might threaten biodiversity in Polish forests, which has been actively conserved and enhanced over recent years. In contrast, some of the strategies suggested by the FCF are likely to have a positive impact on habitat availability relative to current forest management. For example, shelterwood systems managed in direction of natural spread of tree species, might be a good strategy to enhance the biodiversity in Polish forests. Other way of implementing the CCAMS together with habitat protection would be to diversify the strategies on the landscape scale. There is still a place for more evaluation of the FCF project, which could be more accurately implemented if such assessment has been done prior launch of the project.